2011
DOI: 10.1016/j.chroma.2011.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Application of comprehensive two-dimensional gas chromatography with time-of-flight mass spectrometry method to identify potential biomarkers of perinatal asphyxia in a non-human primate model

Abstract: Perinatal asphyxia is a leading cause of brain injury in infants, occurring in 2-4 per 1000 live births. The clinical response to asphyxia is variable and difficult to predict with current diagnostic tests. Reliable biomarkers are needed to help predict the timing and severity of asphyxia, as well as response to treatment. Two-dimensional gas chromatography-time-of-flight-mass spectrometry (GC x GC-TOFMS) was used herein, in conjunction with chemometric data analysis approaches for metabolomic analysis in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 47 publications
5
70
0
Order By: Relevance
“…This may also reflect the body’s transition from more anaerobic metabolism with less oxygen available to predominantly aerobic metabolism utilizing the TCA cycle. In our previous study on the discovery of biomarkers of perinatal asphyxia (24), two intermediates of the TCA cycle were isolated: succinic acid and malic acid. In that study, these two intermediates showed dramatic elevation following birth and asphyxia, which was thought to be a result of an interruption of the redox reaction with nicotinamide adenine dinucleotide/flavin adenine dinucleotide due to the hypoxia insult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may also reflect the body’s transition from more anaerobic metabolism with less oxygen available to predominantly aerobic metabolism utilizing the TCA cycle. In our previous study on the discovery of biomarkers of perinatal asphyxia (24), two intermediates of the TCA cycle were isolated: succinic acid and malic acid. In that study, these two intermediates showed dramatic elevation following birth and asphyxia, which was thought to be a result of an interruption of the redox reaction with nicotinamide adenine dinucleotide/flavin adenine dinucleotide due to the hypoxia insult.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported the use of GC × GC–TOFMS in conjunction with innovative chemometric data analysis tools to characterize the metabolic effects of birth asphyxia in a nonhuman primate model (24). We now describe the biochemical changes that occur as nonhuman primates transition to extrauterine life in the absence of experimental asphyxia.…”
Section: Introductionmentioning
confidence: 99%
“…Fisher ratio analysis is very useful to identify the major compounds responsible for the differences between 2 classes, especially, for example, in the case of on/off responses to illnesses [49]. However, it gives no information regarding changes in the concentration of the analytes present in several classes.…”
Section: Statistical Comparison Using Pairwise Fisher Ratiomentioning
confidence: 99%
“…Fluid-based metabolomics is an increasingly popular area of research in perinatal medicine, with studies related to neonatal encephalopathy and chorioamnionitis [26,[50][51][52] . Attempts have even been made to correlate metabolic changes with neuropathology in a sheep model of inflammation-driven perinatal brain injury [53] .…”
Section: Time-series Analysismentioning
confidence: 99%